Infertile landscapes on an old oceanic island: the biodiversity hotspot of New Caledonia. (6th November 2020) - Pillon, Yohan; Jaffré, Tanguy; Birnbaum, Philippe; Bruy, David; Cluzel, Dominique; Ducousso, Marc; Fogliani, Bruno; Ibanez, Thomas; Jourdan, Hervé; Lagarde, Louis; Léopold, Audrey; Munzinger, Jérôme; et al.
Abstract: The OCBIL theory comprises a set of hypotheses to comprehend the biota of old, climatically buffered, infertile landscapes (OCBILs). Here, we review evidence from the literature to evaluate the extent to which this theory could apply to the biodiversity hotspot of New Caledonia. We present geological, pedological and climatic evidence suggesting how the island might qualify as an OCBIL. The predictions of OCBIL theory are then reviewed in the context of New Caledonia. There is evidence for a high rate of micro-endemism, accumulation of relict lineages, a high incidence of dioecy, myrmecochory and nutritional specializations in plants. New Caledonian vegetation also exhibits several types of monodominant formations that reveal the importance of disturbances on the island. Fires and tropical storms are likely to be important factors that contribute to the dynamic of New Caledonian ecosystems. Although naturally infertile, there is archaeological evidence that humans developed specific horticultural practices in the ultramafic landscapes of New Caledonia. Further comparisons between New Caledonia and other areas of the world, such as South Africa and Southwest Australia, are desirable, to develop the OCBIL theory into a more robust and generalized, testable framework and to determine the most efficient strategies to preserve their outstanding biodiversity.